AMBIGUITAS FRASA MENYERANG KEHORMATAN DALAM PASAL 27A UU ITE 2024 PELANGGARAN ASAS KEPASTIAN HUKUM DAN ANCAMAN TERHADAP KEBEBASAN BERPENDAPAT DI MEDIA SOSIAL - Arief Gunawan Hamka Asiali (Jurnal Perspektif Hukum, 2026)
Article 27A of Law Number 1 of 2024 concerning the Second Amendment to the ITE Law employs the phrase "attacking honour" without a clear objective definition. This doctrinal legal research analyzes the ambiguity of this phrase and its implications for the principle of legal certainty and freedom of expression on social media. The findings indicate that the absence of standard parameters regarding the meaning of honour, the boundary between criticism and defamation, and measurable harm renders this norm multi-interpretable. This condition violates Article 1 paragraph (3) and Article 28D paragraph (1) of the 1945 Constitution concerning legal certainty, and grants excessive discretion to law enforcement officials. Consequently, society experiences a systemic chilling effect, fearing to voice public criticism due to unpredictable criminal threats. Cases involving Saiful Mahdi, Benny Handoko, and Daniel Tangkilisan provide empirical evidence of criminalization against critical expression. This study recommends constitutional judicial review of Article 27A, a moratorium on law enforcement, and the issuance of Supreme Court interpretive guidelines to strictly distinguish between protected criticism and punishable defamation. Without normative reconstruction, freedom of expression as a pillar of democracy will remain threatened.